A high melt strength polyglycolide material and preparation method thereof

By using cashewol glycidyl ether as an additive, a high melt strength grafted polyglycolide material is formed through free radical reaction, which solves the problems of excessive melt flow rate and low melt strength of polyglycolide material, and has achieved a significant improvement in material performance and is suitable for many fields.

CN119192553BActive Publication Date: 2025-04-18EAST CHINA UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411465432.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-04-18
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing polyglycolide materials have too large melt flow rate and too low melt strength during processing, which limits their application in related fields.

Method used

The high melt strength grafted polyglycolide material is formed by reacting free radicals with polyglycolide under the action of peroxide initiator using cashewol glycidyl ether as an additive.

Benefits of technology

The melt strength of polyglycolide materials has been significantly improved, making them suitable for agricultural production, food packaging and biomedicine fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192553B_ABST
    Figure CN119192553B_ABST
Patent Text Reader

Abstract

The invention discloses a high melt strength polyglycolide material and a preparation method thereof, and belongs to the technical field of polymer material processing and modification. The raw materials of the high melt strength polyglycolide material include: 100 parts of polyglycolide, 0.1-10 parts of auxiliary agent, and 0.01-3 parts of initiator; the auxiliary agent is cardanol glycidyl ether; the preparation method includes the following steps: polyglycolide, auxiliary agent and initiator are uniformly mixed to obtain a mixed material, and the mixed material is melt-extruded to obtain the high melt strength polyglycolide material. During the melt extrusion process, under the action of a peroxide initiator, the double bond of the auxiliary agent reacts with the secondary carbon of the polyglycolide molecule by free radical reaction, and then the epoxy group and the terminal hydroxyl group or terminal carboxyl group of the polyglycolide molecule undergo a ring-opening reaction to obtain a high melt strength grafted polyglycolide material. The preparation method of the invention is simple, and the obtained high melt strength polyglycolide material can be used in agricultural production, food packaging, biomedicine and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material processing and modification, in particular to a high melt strength polyglycolide material and a preparation method thereof. Background Art

[0002] Polyglycolide (PGA), as a simple linear aliphatic polyester, is recognized in the world as a material for protecting the earth's environment and life. It has excellent degradability and excellent force barrier properties. Due to its good biocompatibility, PGA has been widely used in medical absorbable surgical sutures, biodegradable polymer stents, controlled drug release, simulated human tissue materials and other products. However, due to the shortcomings of PGA such as excessive melt flow rate and low melt strength at processing temperature, the application of PGA in related fields is severely limited.

[0003] The melt strength of PGA can be improved by increasing the relative molecular weight, chain extension or cross-linking. The construction of the cross-linked structure usually adopts the reactive extrusion method. The principle is to use the initiator to trigger the auxiliary agent in the internal mixer to produce small molecular free radicals, which react with the secondary carbon and hydrogen of the PGA molecular chain to form macromolecular free radicals, and branching or cross-linking reactions occur with the participation of the auxiliary agent, thereby improving the melt strength of PGA.

[0004] At present, most of the commonly used additives are petroleum-based additives, but they cannot avoid causing environmental pollution. Moreover, the performance of the obtained PGA material is not very good and still needs to be improved. Therefore, it is necessary to develop a bio-based additive to replace the traditional petroleum-based additives, so as to reduce the dependence on petroleum resources and obtain PGA materials with better performance. Summary of the invention

[0005] The purpose of the present invention is to provide a high melt strength polyglycolide material and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The high melt strength polyglycolide material of the present invention has excellent performance and is suitable for agricultural production, food packaging, biomedicine and other fields.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention is: a high melt strength polyglycolide material (actually polyglycolide grafted with cardanol glycidyl ether), wherein the raw materials include the following components by weight:

[0008] 100 parts of polyglycolide, 0.1-10 parts of auxiliary agent, 0.01-3 parts of initiator;

[0009] The auxiliary agent is cardanol glycidyl ether (ECA);

[0010] The structural formula of the cardanol glycidyl ether is Wherein, n=0, 2, 4 or 6.

[0011] Furthermore, the melt index of the polyglycolide is 5 to 25 g / 10 min.

[0012] Furthermore, the initiator is a peroxide initiator.

[0013] Furthermore, the peroxide initiator is di-tert-butyl peroxyisopropylbenzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, dibenzoyl peroxide or 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.

[0014] Furthermore, the middle:

[0015] When n = 0, -C 15 H 31-n The structural formula is

[0016] When n = 2, -C 15 H 31-n The structural formula is

[0017] When n = 4, -C 15 H 31-n The structural formula is

[0018] When n = 6, -C 15 H 31-n The structural formula is

[0019] Furthermore, the cardanol glycidyl ether comprises, by weight percentage:

[0020] n=0 0~10%, not 0;

[0021] n=2 0~54%, and not 0;

[0022] n=4 0~43%, not 0;

[0023] n=6 0~61%, and not 0.

[0024] The second technical solution of the present invention: The preparation method of the above-mentioned high melt strength polyglycolide material comprises the following steps: polyglycolide, an auxiliary agent and an initiator are uniformly mixed to obtain a mixed material, and the mixed material is melt-extruded to obtain the high melt strength polyglycolide material.

[0025] During the melt extrusion process, under the action of peroxide initiators, the double bonds of the additive react with the secondary carbon of the polyglycolide molecule in a free radical reaction, and then the epoxy group and the terminal hydroxyl or carboxyl group of the polyglycolide molecule undergo a ring-opening reaction to obtain a high melt strength grafted polyglycolide material. The reaction equation in the reaction system is as follows:

[0026] When n=0, the reaction equation is:

[0027]

[0028] When n=2, the reaction equation is:

[0029]

[0030] When n=4, the reaction equation is:

[0031]

[0032] When n=6, the reaction equation is:

[0033]

[0034] The structural formula of ORO is:

[0035] (When the peroxide initiator is di-tert-butyl peroxyisopropylbenzene);

[0036] (when the peroxide initiator is dicumyl peroxide);

[0037] (when the peroxide initiator is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane);

[0038] (When the peroxide initiator is 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane);

[0039] or (When the peroxide initiator is dibenzoyl peroxide).

[0040] Furthermore, the mixing is carried out in a high-speed mixer.

[0041] Furthermore, the mixing speed is 500-2000 rpm, and the mixing time is 5-15 min.

[0042] Furthermore, the melt extrusion is carried out in an internal mixer or a twin-screw extruder.

[0043] Furthermore, the melt extrusion temperature is 230-260° C., the rotation speed is 90-200 rpm, and the time is 1-5 min.

[0044] The third technical solution of the present invention: application of the above-mentioned high melt strength polyglycolide material in agricultural production, food packaging or biomedical fields.

[0045] The present invention discloses the following technical effects:

[0046] The auxiliary agent used in the present invention is cardanol glycidyl ether, which has unsaturated double bonds and epoxy groups. The unsaturated double bonds can be triggered by peroxides to undergo free radical reactions under high temperature conditions, and the epoxy groups are easy to undergo ring-opening reactions with functional groups such as terminal hydroxyl groups or terminal carboxyl groups of polyglycolide. Cardanol glycidyl ether containing epoxy groups is obtained by replacing the phenolic hydroxyl groups of cardanol with epoxy groups, and has the characteristics of low cost, good renewability and abundant sources.

[0047] The invention uses polyglycolide and an auxiliary agent (cardanol glycidyl ether) as main raw materials. Under the action of a peroxide initiator, the double bonds on the auxiliary agent are bonded to the secondary carbon of the polyglycolide molecule, and then the epoxy group and the terminal hydroxyl group or carboxyl group of the polyglycolide molecule undergo a chain extension reaction, which can effectively increase the branching degree of the polyglycolide, so that the prepared bio-based grafted polyglycolide material has the characteristics of high melt strength. The preparation method is simple and meets the requirements of agricultural production, food packaging, biomedicine and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0049] Figure 1 The relationship between the complex viscosity of the grafted PGA of Example 1-2 and Comparative Example 1-2 and pure PGA in the dynamic rheological test and the frequency;

[0050] Figure 2 The Cole-Cole curves of the grafted PGA and pure PGA of Examples 1-2 and Comparative Examples 1-2;

[0051] Figure 3 The relaxation time spectra of the grafted PGA of Example 1-2 and Comparative Example 1-2 and pure PGA. DETAILED DESCRIPTION

[0052] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0053] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0054] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0055] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0056] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0057] The present invention provides a high melt strength polyglycolide material, wherein the raw materials include the following components by weight:

[0058] 100 parts of polyglycolide, 0.1-10 parts of auxiliary agent, 0.01-3 parts of initiator;

[0059] The auxiliary agent is cardanol glycidyl ether (ECA);

[0060] The structural formula of the cardanol glycidyl ether is Wherein, n=0, 2, 4 or 6;

[0061] When n = 0, -C 15 H 31-n The structural formula is

[0062] When n = 2, -C 15 H 31-n The structural formula is

[0063] When n = 4, -C 15 H 31-n The structural formula is

[0064] When n = 6, -C 15 H 31-n The structural formula is

[0065] The cardanol glycidyl ether comprises, by weight percentage:

[0066] n=0 0~10%, not 0;

[0067] n=2 0~54%, and not 0;

[0068] n=4 0~43%, not 0;

[0069] n=6 0~61%, and not 0.

[0070] As a preferred embodiment of the present invention, the melt index of the polyglycolide is 5 to 25 g / 10 min, and the number average molecular weight is 116239-152380 g / mol.

[0071] As a preferred embodiment of the present invention, the peroxide initiator is di-tert-butyl peroxyisopropylbenzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, dibenzoyl peroxide or 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane.

[0072] The present invention also provides a method for preparing the above-mentioned high melt strength polyglycolide material, comprising the following steps:

[0073] The polyglycolide, the auxiliary agent and the initiator are uniformly mixed to obtain a mixture, and the mixture is melt-extruded to obtain the polyglycolide material with high melt strength.

[0074] The reaction equation in the reaction system is as follows:

[0075] When n=0, the reaction equation is:

[0076]

[0077] When n=2, the reaction equation is:

[0078]

[0079] When n=4, the reaction equation is:

[0080]

[0081] When n=6, the reaction equation is:

[0082]

[0083] The structural formula of ORO is:

[0084] (When the peroxide initiator is di-tert-butyl peroxyisopropylbenzene);

[0085] (when the peroxide initiator is dicumyl peroxide);

[0086] (when the peroxide initiator is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane);

[0087] (When the peroxide initiator is 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane);

[0088] or (When the peroxide initiator is dibenzoyl peroxide).

[0089] As a preferred embodiment of the present invention, the mixing is carried out in a high-speed mixer; the mixing speed is 500 to 2000 rpm, and the mixing time is 5 to 15 minutes.

[0090] As a preferred embodiment of the present invention, the melt extrusion is carried out in an internal mixer or a twin-screw extruder; the melt extrusion temperature is 230-260° C., the rotation speed is 90-200 rpm, and the time is 1-5 min.

[0091] The present invention also provides application of the high melt strength polyglycolide material in agricultural production, food packaging or biomedical fields.

[0092] The technical solution of the present invention is further described below through specific embodiments.

[0093] All raw materials used in the embodiments of the present invention can be purchased commercially. Among them, the PGA raw material has a melt index (MFR) of 15.8 g / 10 min and is purchased from Shanghai Pujing Chemical Technology Co., Ltd.

[0094] Cardanol glycidyl ether n = 0 The content of is 0-10wt%, n=2 The content of is 0 to 54 wt%, n = 4 The content of is 0-43wt%, n=6 The content of is 0-61wt%, and cardanol glycidyl ether is purchased from Kaled Chemical Zhuhai Co., Ltd.

[0095] Example 1

[0096] 100 g of polyglycolide, 0.1 g of auxiliary cardanol glycidyl ether (wherein the content of the component with n=0 is 3 wt %, the content of the component with n=2 is 40 wt %, the content of the component with n=4 is 37 wt %, and the content of the component with n=6 is 20 wt %) and 0.05 g of initiator di-tert-butyl peroxyisopropylbenzene are added to a high-speed mixer at a mixer speed of 500 rpm for 15 min to obtain a mixed material, and the mixed material is fed into a twin-screw extruder for melt extrusion at a melt extrusion temperature of 240° C., a main engine speed of 100 rpm, and an extrusion time of 3 min to obtain a high melt strength polyglycolide material grafted with cardanol glycidyl ether.

[0097] Example 2

[0098] 100 g of polyglycolide, 3.5 g of auxiliary agent cardanol glycidyl ether (wherein the content of the component with n=0 is 1 wt %, the content of the component with n=2 is 37 wt %, the content of the component with n=4 is 23 wt %, and the content of the component with n=6 is 39 wt %) and 1.2 g of initiator dicumyl peroxide are added to a high-speed mixer at a mixer speed of 800 rpm for 12 min to obtain a mixed material, and the mixed material is fed into a twin-screw extruder for melt extrusion at a melt extrusion temperature of 250° C., a main engine speed of 100 rpm, and an extrusion time of 3 min to obtain a high melt strength polyglycolide material grafted with cardanol glycidyl ether.

[0099] Example 3

[0100] 100 g of polyglycolide, 6.0 g of auxiliary agent cardanol glycidyl ether (wherein the content of the component with n=0 is 2 wt%, the content of the component with n=2 is 30 wt%, the content of the component with n=4 is 21 wt%, and the content of the component with n=6 is 47 wt%) and 2.0 g of initiator 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane are added to a high-speed mixer at a mixer speed of 1500 rpm for 10 min to obtain a mixed material, and the mixed material is fed into a twin-screw extruder for melt extrusion at a melt blending temperature of 260° C., a main engine speed of 90 rpm, and an extrusion time of 2 min to obtain a high melt strength polyglycolide material grafted with cardanol glycidyl ether.

[0101] Example 4

[0102] 100 g of polyglycolide, 8.5 g of auxiliary agent cardanol glycidyl ether (wherein the content of the component with n=0 is 3 wt %, the content of the component with n=2 is 22 wt %, the content of the component with n=4 is 33 wt %, and the content of the component with n=6 is 42 wt %) and 3.0 g of initiator dibenzoyl peroxide are added to a high-speed mixer at a mixer speed of 2000 rpm for 8 min to obtain a mixed material, and the mixed material is fed into a twin-screw extruder for melt extrusion at a melt blending temperature of 220° C., a main engine speed of 150 rpm, and an extrusion time of 4 min to obtain a high melt strength polyglycolide material grafted with cardanol glycidyl ether.

[0103] Example 5

[0104] 100 g of polyglycolide, 10.0 g of auxiliary agent cardanol glycidyl ether (wherein the content of the component with n=0 is 3 wt%, the content of the component with n=2 is 40 wt%, the content of the component with n=4 is 27 wt%, and the content of the component with n=6 is 30 wt%) and 2.5 g of initiator 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane are added to a high-speed mixer at a mixer speed of 1000 rpm for 8 min to obtain a mixed material, and the mixed material is fed into a twin-screw extruder for melt extrusion at a melt blending temperature of 240° C., a main engine speed of 130 rpm, and an extrusion time of 5 min to obtain a high melt strength polyglycolide material grafted with cardanol glycidyl ether.

[0105] Example 6

[0106] Same as Example 1, except that the melt extrusion temperature is 250°C and the main engine speed is 200 rpm.

[0107] Example 7

[0108] The same as Example 2, except that the mixing speed is 2000 rpm and the mixing time is 5 min.

[0109] Comparative Example 1

[0110] Same as Example 1, except that an equal amount of cardanol glycidyl ether is replaced by cardanol (R1 is -C 15 H 31-n , wherein the content of the component with n=0 is 3wt%, the content of the component with n=2 is 40wt%, the content of the component with n=4 is 37wt%, and the content of the component with n=6 is 20wt%).

[0111] Comparative Example 2

[0112] The same as Example 1, except that an equal amount of cardanol glycidyl ether is replaced by pentaerythritol triacrylate (PETA).

[0113] Test Case

[0114] The grafted polyglycolide materials prepared in Examples 1 to 7 and Comparative Examples 1 to 2 and the raw material PGA were used to prepare mechanical specimens using a micro injection molding machine. Specifically, the samples were crushed and melted at 265°C for 4 minutes before injection molding. During the injection molding process, the mold temperature was 90°C, the injection pressure was 650 bar, the holding pressure was 600 bar, the injection time was 25 s, and the holding time was 20 s. The impact specimens were obtained by milling out a 2 mm deep A-notch using a V-notch machine after the bending specimens were injection molded. All specimens were stored at 23°C for 48 hours before mechanical property tests. The test standard adopted ISO 527. The specific results are shown in Tables 1 and Figure 1-3 Among them, the melt strength in Table 1 is calculated by the melt flow index MFR value (when the polymer is extruded from the melt flow tester, the melt viscosity at a very low shear rate can be calculated by measuring the change in the diameter of the extruded part. The melt viscosity calculated in this way is called melt strength).

[0115] Table 1 Performance data of PGA of Examples and Comparative Examples

[0116]

[0117] Figure 1 The relationship between the complex viscosity of the grafted PGA of Example 1-2 and Comparative Example 1-2 and pure PGA (raw material PGA) in the dynamic rheology test and the frequency (which can characterize the melt strength of the polymer).

[0118] From the data in Table 1 and Figure 1It can be seen that the polyglycolide material prepared by the present invention has the characteristics of high melt strength. The melt strength of PGA after grafting modification is significantly improved, which can be increased to more than 2 times of that of ungrafted PGA, and the impact strength is also greatly improved, indicating that the effect of grafting modification is obvious. Although the melt strength of PGA in the comparative example is improved to a certain extent, the effect is far worse than that of the embodiment.

[0119] Figure 2 The Cole-Cole curves of the grafted PGA and pure PGA of Examples 1-2 and Comparative Examples 1-2 are generally used to distinguish the linear and nonlinear structures of polymers. The Cole-Cole curve of a linear polymer is close to a semicircle, while for a nonlinear structure, the larger the curve radius, the more branched the polymer structure. Figure 2 It can be seen that the curve radius of the embodiment is significantly larger than that of the comparative example.

[0120] Figure 3 The relaxation time spectra of the grafted PGA and pure PGA of Example 1-2 and Comparative Example 1-2 are shown in FIG. Figure 3 It can be seen that under the same τ condition, the relaxation time of the grafted PGA of the embodiment is longer than that of the grafted PGA of the comparison example.

[0121] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A high melt strength polyglycolide material, characterized in that: The raw materials include the following components by mass: 100 parts of polyglycolide, 0.1-10 parts of auxiliary agent, 0.01-3 parts of initiator; The auxiliary agent is cardanol glycidyl ether; The structural formula of the cardanol glycidyl ether is Wherein, n=0, 2, 4 or 6; The cardanol glycidyl ether comprises, by weight percentage: n=0 0~10%, not 0; n = 2 0~54%, and not 0; n=4 0~43%, not 0; n=6 0~61%, and not 0.

2. The high melt strength polyglycolide material according to claim 1, characterized in that: The melt index of the polyglycolide is 5 to 25 g / 10 min.

3. The high melt strength polyglycolide material according to claim 1, characterized in that: The initiator is a peroxide initiator.

4. The high melt strength polyglycolide material according to claim 3, characterized in that: The peroxide initiator is di-tert-butyl peroxy isopropylbenzene, diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexane, dibenzoyl peroxide or 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexane.

5. The high melt strength polyglycolide material according to claim 1, characterized in that: Said middle: When n = 0, -C 15 H 31-n The structural formula is When n = 2, -C 15 H 31-n The structural formula is When n = 4, -C 15 H 31-n The structural formula is When n = 6, -C 15 H 31-n The structural formula is 6. The method for preparing a high melt strength polyglycolide material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The polyglycolide, the auxiliary agent and the initiator are uniformly mixed to obtain a mixture, and the mixture is melt-extruded to obtain the polyglycolide material with high melt strength.

7. The preparation method according to claim 6, characterized in that: The mixing speed is 500-2000 rpm and the mixing time is 5-15 min.

8. The preparation method according to claim 6, characterized in that: The temperature of the melt extrusion is 230-260° C., the rotation speed is 90-200 rpm, and the time is 1-5 min.

9. Use of the high melt strength polyglycolide material according to any one of claims 1 to 5 in agricultural production, food packaging or biomedical fields.

Citation Information

Patent Citations

  • High-crystallinity heat-resistant polylactic acid material and preparation method thereof

    CN114106310A